Upaya Pengembangan Kinerja Ilmiah Siswa melalui Lembar Kerja Proyek pada Fermentasi Cuka Limbah Kulit Semangka - Nisa Putri Utami; Riri Aisyah; Nurhayati Nurhayati; Ida Farida; Sari Sari (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to describe the activities and develop students' scientific performance using project-based worksheets on vinegar fermentation from watermelon rind waste. The subjects were 20 students from the Youth Scientific Group (KIR) at Jatinangor State Senior High School. This study was a pre-experimental study with a one-shot case study design. The study was conducted based on the importance of scientific performance skills for students, as it trains them to think critically, logically, and systematically in solving problems, preparing them to face the demands of 21st-century skills. Through scientific processes such as observation, practicum, and data analysis, students gain a deeper understanding of concepts and foster curiosity and creativity. The results showed that the average student worksheet score was categorized as very good (82), the average student activity score was categorized as very good (91.6), and the student scientific performance assessment reached 91.8, categorized as very good. These findings indicate that the application of project-based worksheets to make vinegar from watermelon rind waste successfully developed students' scientific activity and performance.